2014
DOI: 10.3109/03009742.2013.852239
|View full text |Cite
|
Sign up to set email alerts
|

Making the invisible visible: bioelectrical impedance analysis demonstrates unfavourable body composition in rheumatoid arthritis patients in clinical practice

Abstract: A high frequency of unfavourable body composition, predominantly reduced FFMI and elevated FMI, was found in a cohort of RA patients with moderately active disease, turning BMI into an unreliable method for assessment of body composition in RA. BIA, however, might be the preferred method to assess FFMI and FMI in RA patients in clinical practice, as it is easy to use and relatively inexpensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…The BMI was used with WHO definitions for underweight, overweight and obesity; however, it does not measure adipose tissue. The body composition might be more precisely represented by waist circumference, dual-energy X-ray absorptiometry, and fat mass indexes using bioelectrical impedance [ 5 , 20 ]. We selected the BMI as a surrogate for obesity and underweight as it was obtained in all arthritis cohorts and in the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…The BMI was used with WHO definitions for underweight, overweight and obesity; however, it does not measure adipose tissue. The body composition might be more precisely represented by waist circumference, dual-energy X-ray absorptiometry, and fat mass indexes using bioelectrical impedance [ 5 , 20 ]. We selected the BMI as a surrogate for obesity and underweight as it was obtained in all arthritis cohorts and in the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study on the Canadian elderly showed that the body fat percentage was 26.5% in men and 40.2% in women ( McIntosh, Smale, & Vallis, 2013 ). Moreover, in Amsterdam, 74% of elderly people had high and very high FMI ( Konijn et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…BMI is also an inadequate detector of LM loss: in a case-control study, BMI was unable to detect rheumatoid cachexia as assessed by DXA in 26% of women and 21% of men [16]. In a cohort of patients with moderately active disease, 44% of women with a normal BMI had low fat-free mass index (FFMI), while 40% of women and 75% of men in the normal BMI category had high or very high fat mass index (FMI) [17]. Despite these limitations, BMI is related to several outcomes in RA, and patients with BMI < 18.5 show the highest CV risk [18] and highest rates of erosive disease [19].…”
Section: Body Composition In Rheumatoid Arthritismentioning
confidence: 96%